From Linear to Circular Food Supply Chains - Despoudi, Stella. author. aut Link
XV, 88 p. 10 illus.
Keywords: This book aims to provide the reader with an understanding of the concept of the circular economy, in relation to food supply chains. The current food supply chain system, based upon the linear supply chain model, is unquestionably unsustainable: make, use, dispose. The circular supply chain model, on the other hand, aims to keep resources in use for as long as possible, while regenerating products/materials at the end of their service life. In short: reduce, reuse, recycle. This book puts forwards the circular economy as an alternative to the traditional supply chain management models. The circular economy aims to minimise material, energy and environmental damage without restricting economic growth and social and technological progress. It involves transition to renewable energy sources, and it builds on economic, natural and social capital. This shortform monograph will appeal to academics working in the fields of supply chain logistics, operation management, agricultural management, and sustainability more broadly. Dr. Stella Despoudi is Lecturer in Operations and Supply Chain Management at Aston University, UK and Adjunct Lecturer in Supply Chain Management at University of Western Macedonia, Greece. Prof. Uthayasankar Sivarajah is Head of School of Management and Professor of Technology Management and Circular Economy at the School of Management, University of Bradford, UK. Dr Manoj Dora is Director of Collaborative Projects and Outreach at Brunel Business School, UK. Manoj's areas of specialisation are Sustainable Value Chain and Quality Management, with a focus on Lean Six Sigma in the agro-food sector.